Didactic Design for Developing Students' Creative Thinking Ability in Solving Open-Ended Problems: An Adversity Quotient Perspective - Nursalam, Nursalam; L Zakiyah Nur S; Andi Kusumayanti (UNNES JOURNAL, 2025)
This study aims to develop students’ creative thinking skills, address their learning obstacles, and describe their creative thinking abilities in relation to their adversity quotient. A qualitative approach was employed using the Didactical Design Research (DDR) method, which consists of three stages: prospective analysis, metapedadidactic analysis, and retrospective analysis. The participants were students from class XA DPIB, selected based on preliminary findings indicating variations in creative thinking skills and levels of adversity quotient (the ability to endure and overcome challenges). Data were collected through both test and non-test techniques, including observation, interviews, questionnaires, and documentation. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing or verification. The results of the prospective analysis revealed the existence of learning obstacles among students, emphasizing the need to identify, analyze, and address these barriers in the learning process. The metapedadidactic analysis indicated that the developed didactical design was effective in overcoming students’ learning difficulties. Meanwhile, the retrospective analysis demonstrated an expansion in the prediction of student responses and an improvement in the quality of didactic-pedagogical anticipation by the teacher. The findings imply that the implementation of a didactical design based on students’ learning obstacles and adversity quotient can serve as an effective strategy for enhancing students’ mathematical creative thinking skills. It can be concluded that the didactical design developed in this study not only succeeded in addressing students’ learning barriers but also effectively improved their mathematical creative thinking skills when viewed from the perspective of their adversity quotient. Abstrak Penelitian ini bertujuan untuk mengembangkan kemampuan berpikir kreatif siswa dan mengatasi hambatan belajarnya, serta mendeskripsikan kemampuan berpikir kreatif siswa ditinjau dari adversity quotient. Penelitian ini menggunakan pendekatan kualitatif dengan metode DDR (Didactical Design Research) yang terdiri dari tiga tahapan, yaitu prospective analysis, metapedadidactic analysis, dan retrospective analysis. Subjek dalam penelitian ini adalah siswa kelas XA DPIB. Pemilihan subjek ini didasarkan pada temuan awal bahwa kelas tersebut menunjukkan variasi dalam kemampuan berpikir kreatif dan tingkat adversity quotient (kemampuan bertahan dan mengatasi kesulitan). Teknik pengumpulan data dilakukan melalui tes dan non-tes, meliputi observasi, wawancara, angket (kuesioner), dan dokumentasi. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Berdasarkan hasil analisis prospektif, ditemukan adanya hambatan belajar pada peserta didik, yang menunjukkan pentingnya identifikasi, analisis, dan penanganan faktor-faktor penghambat dalam proses pembelajaran. Selanjutnya, dari hasil analisis metapedadidaktik diketahui bahwa desain didaktis yang dikembangkan terbukti efektif dalam mengatasi hambatan belajar siswa. Sementara itu, hasil analisis retrospektif menunjukkan adanya perluasan dalam prediksi respon siswa dan peningkatan kualitas antisipasi didaktis-pedagogis oleh guru. Implikasi dari penelitian ini adalah bahwa penerapan desain didaktis berbasis hambatan belajar dan karakter adversity quotient siswa dapat menjadi strategi yang efektif dalam meningkatkan kemampuan berpikir kreatif matematis. Dengan demikian, dapat disimpulkan bahwa desain didaktis yang dikembangkan dalam penelitian ini tidak hanya mampu mengatasi hambatan belajar siswa, tetapi juga berhasil meningkatkan kemampuan berpikir kreatif matematis siswa ditinjau dari adversity quotient-nya.